2010
DOI: 10.1007/s00213-010-1787-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aripiprazole, risperidone, and olanzapine on the acoustic startle response in Japanese chronic schizophrenia

Abstract: Aripiprazole and risperidone may improve PPI90. ASR, HAB, PPI82, and PPI86 were no different among the Japanese schizophrenic patient groups with different antipsychotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Disruption of PPI in rats is at least partly due to activation of D 2 r (Swerdlow et al, 1991), suggesting that increased activity at these receptors might also be a substrate for PPI deficits in schizophrenia. In this sense, patients with schizophrenia present significant differences in the acoustic startle reflex, habituation to startle stimuli, and several PPI levels compared with healthy controls (Moriwaki et al, 2009), and antipsychotic treatment with olanzapine, aripiprazole, and risperidone improve PPI, but do not modify the acoustic startle reflex or habituation (Kishi et al, 2010;Wynn et al, 2007). Another study using a longitudinal within-subjects design reported improved results after switching from the conventional antipsychotic zuclopenthixol to long-acting injectable risperidone (Martinez-Gras et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of PPI in rats is at least partly due to activation of D 2 r (Swerdlow et al, 1991), suggesting that increased activity at these receptors might also be a substrate for PPI deficits in schizophrenia. In this sense, patients with schizophrenia present significant differences in the acoustic startle reflex, habituation to startle stimuli, and several PPI levels compared with healthy controls (Moriwaki et al, 2009), and antipsychotic treatment with olanzapine, aripiprazole, and risperidone improve PPI, but do not modify the acoustic startle reflex or habituation (Kishi et al, 2010;Wynn et al, 2007). Another study using a longitudinal within-subjects design reported improved results after switching from the conventional antipsychotic zuclopenthixol to long-acting injectable risperidone (Martinez-Gras et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have provided evidence that PPI deficits in patients with schizophrenia are improved by antipsychotics,24,37,38,40,42,59-67) in particular atypical antipsychotics, which appear to have a close association with PPI improvement in schizophrenia 24,42,59-61,63,64,66,68-70). Although PPI has been reported in association with positive symptoms65,71) and negative symptoms,71,72) thought disorders73) and social perception74) of schizophrenia, most studies do not support a link between PPI and psychiatric symptoms 24,63,70,75).…”
Section: Ppi In Schizophreniamentioning
confidence: 99%
“…However, these agents tended to be prescribed in low doses, usually with a tapering schedule until discontinuation. Only patients prescribed antipsychotic were excluded, because these agents are known to influence SRs and PPI (Martinez-Gras et al, 2009;Kishi et al, 2010).…”
Section: Patientsmentioning
confidence: 99%